Selected physicochemical properties of starches isolated from ten cassava varieties reveal novel industrial uses - Justamante Händel Schmitz, Gabriela; Gonçalves Peroni-Okita, Fernanda Helena; Oliveira do Nascimento, João Roberto; Bombarda Campanha, Raquel; Losada Valle, Teresa; Landi Franco, Célia Maria [UNESP]; Cordenunsi-Lysenko, Beatriz Rosana (Wiley, 2017)
Although cassava is of great importance as a starch source for industrial purposes or food consumption, the evaluation of different varieties is an under-investigated topic. Thus, in order to contribute to the identification of cassava starches more suitable for use and application in the food industry, this study aimed to analyze and compare the physicochemical properties of starches from ten different cassava varieties of household consumption, industrial use, and mixed use. In order to accomplish this goal, analyses were performed into the thermal and pasting properties, granule size, and amylopectin branch-chain-length distribution and amylose and phosphorus contents, as well as scanning electron microscopy (SEM) images of the starches. In addition, a principal component analysis (PCA) biplot was generated, as one of the most useful methods to analyze multidimensional datasets with quantitative variables. Significant differences in phosphorus and amylose contents, branch-chain-length distribution of amylopectin, starch granule diameter, gelatinization and retrogradation temperatures, and pasting properties were obtained. Therefore, this study adds to the literature regarding the physicochemical properties of starches of these cassava varieties, contributing to improving their uses in the food industry by novel applications these starches, and adding and corroborating uses of some varieties studied.
Keywords: Bitter cassava; Manihot esculenta Crantz; Physicochemical properties; Sweet cassava